Pretransplant solid organ malignancy and organ transplant candidacy: A consensus expert opinion statement. Issue 2 (23rd October 2020) - Al‐Adra, David P.; Hammel, Laura; Roberts, John; Woodle, E. Steve; Levine, Deborah; Mandelbrot, Didier; Verna, Elizabeth; Locke, Jayme; D'Cunha, Jonathan; Farr, Maryjane; Sawinski, Deirdre; Agarwal, Piyush K.; et al.
Abstract : Patients undergoing evaluation for solid organ transplantation (SOT) often have a history of malignancy. Although the cancer has been treated in these patients, the benefits of transplantation need to be balanced against the risk of tumor recurrence, especially in the setting of immunosuppression. Prior guidelines of when to transplant patients with a prior treated malignancy do not take in to account current staging, disease biology, or advances in cancer treatments. To develop contemporary recommendations, the American Society of Transplantation held a consensus workshop to perform a comprehensive review of current literature regarding cancer therapies, cancer stage‐specific prognosis, the kinetics of cancer recurrence, and the limited data on the effects of immunosuppression on cancer‐specific outcomes. This document contains prognosis based on contemporary treatment and transplant recommendations for breast, colorectal, anal, urological, gynecological, and nonsmall cell lung cancers. This conference and consensus documents aim to provide recommendations to assist in the evaluation of patients for SOT given a history of a pretransplant malignancy. Abstract : This article presents consensus expert opinion transplant recommendations for patients with a prior breast, colorectal, anal, urological, gynecological, or non‐small cell lung cancer. See the companion review on page 475 and an editorial from Hart and Engels on page 447 .